The Influence on Strategic Partnerships Through Market Attractiveness and Distinctive Competencies (A Study on Tourism Services Industry in Maluku Province) - Sammy Saptenno; Dady Mairuhu; Julius Buyang; Imelda Talahatu; Dian Utami Sutiksno (Journal of International Conference Proceedings (JICP), 2021)
Maluku is a strategic area as a tourism destination because it has unique characteristics, but tourism service managers are less than optimal in utilizing market attractiveness, and they lack the distinctive competencies of the company. In addition, strategic partnerships with stakeholders have not been developed optimally. This study uses an economics approach that is acculturated with strategic management science with a focus on the level of management understanding of market attractiveness, distinctive competencies and strategic partnerships in the tourism service industry in Maluku Province.  The research method is using a survey method which includes a descriptive survey and an explanatory survey. The unit of analysis in this study is the tourism service industry in Maluku with the unit of observation being the head of a tourism service company in Maluku. The test was carried out using a structural equation model.  The results show that the perceived market attractiveness is not yet fully attractive to tourism service companies in Maluku, distinctive competencies and strategic partnerships have not been maximally developed by tourism service companies in Maluku. The test results also show that there is a simultaneous or partial effect of market attractiveness and distinctive competencies on strategic partnerships. Strategic partnerships are more dominantly formed by distinctive competencies and the dimension that gives the highest contribution is organizational capability.